The potential role of bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) single‐tablet regimen in the expanding spectrum of fixed‐dose combination therapy for HIV. (4th February 2020) - Stellbrink, H‐J; Lazzarin, A; Woolley, I; Llibre, JM
Abstract : Single‐tablet regimens (STRs) of highly safe and effective combination antiretroviral therapy (cART) have had a significant beneficial impact on the clinical outcomes and lives of people living with HIV (PLHIV). As a consequence, healthcare professionals caring for PLHIV in high‐income countries have increasingly focused on issues beyond those related to HIV itself, i.e. HIV‐related neurological disease, or associated opportunistic infections, which include co‐infections, and primarily age‐ and lifestyle‐related comorbidities such as cardiovascular disease, diabetes mellitus, renal impairment, osteoporosis and frailty. This review considers drug side effects and comorbidities seen in PLHIV and evaluates the role of a recently licensed STR – bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) – in mitigating some of those challenges. Factors that need to be evaluated for initial cART regimens include: pretreatment CD4 cell count; plasma HIV RNA; HIV drug resistance; hepatitis B co‐infection; HLA‐B*5701 status; drug‐drug interactions; pregnancy and pregnancy potential; psychiatric and physical comorbidities such as renal or bone disease, as well as simplicity and adherence‐friendliness, all of which need to be considered in all lines of therapy. BIC/FTC/TAF constitutes a new STR that includes an unboosted integrase strand transfer inhibitor with a high barrier against resistance with TAF and FTC. Its virological efficacy was non‐inferior to dolutegravir‐based regimens previously recommended by most guidelines for treatment initiation in large double‐blind, randomised clinical trials in treatment‐naïve or switch patients over 96 weeks. Tolerability and pharmacological properties of the regimen make it a useful tool to address several of the clinical management issues raised above.